Ethics, an administrative perspective of academic programs (REICE: Revista Electrónica de Investigación en Ciencias Económicas, 2023)
Objective: The purpose of the study was framed in reflecting on ethics in the public accounting and business administration programs of the Francisco de Paula Santander Ocaña University. Method: methodologically, qualitative documentary research was used, for which a review of the curricular mesh of the programs and the microcurriculum of the subjects was carried out, for the collection of said information an information record sheet was organized; Likewise, databases and academic publications were consulted. Results: the programs teach the subject of ethics in the last semesters and during their professional training there are no contents contemplated that address the subject; ethics is approached from the point of view of their professional area and not as a transversal training in their lives. Discussions: Universities as training entities not only disciplinary but as generators of professionals, have not done the work that corresponds to them, since they have worked to achieve academic quality, but have neglected the formation of being, of the greatness of the individuals. Conclusions: Ethics must be approached as a way of life, since it bases the human act to act with ethics, dignifies the being and society.
Keywords: Ethics; professional ethics; morality